EFEKTIVITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN PNEUMONIA ANAK DI INSTALASI RAWAT INAP DI RSUD ULIN BANJARMASIN TAHUN 2022 - Nazhipah Isnani; Muliyani; Muhammad Zaini; Muhammad Muhatadin Jamil; Hadiah Akbar, Nabila (Jurnal Insan Farmasi Indonesia, 2024)
Pneumonia is a disease that is a problem in various developing countries, including Indonesia. Pneumonia that occurs in Indonesia tends to increase with age. This research is descriptive research with a retrospective data collection method using a sampling technique, namely total sampling. The retrospective was carried out based on previous data, referring to secondary data in the form of patient medical records while being treated at the Ulin Hospital, Banjarmasin, a sample of 98 medical records of pediatric pneumonia patients at the Ulin Banjarmasin Hospital inpatient installation for the period January-December 2022. Based on the research results obtained that patients suffering from pneumonia experienced fever for a maximum of 1-3 days totaling 87 people (89%). The highest number of antibiotics used was a single antibiotic in the cephalosporin group, namely 33 people (32%). Based on the effectiveness of antibiotics based on the duration of fever, the use of Ampicillin+gentamicin in 32 patients (31%) reduced fever more within a period of 1-3 days.